Meningkatkan Minat Belajar Sejarah Siswa Melalui Model Quantum Teaching - Ayu Lestari; Wahidul Basri; Aisiah Aisiah (PAKAR Pendidikan, 2019)
This research was motivated by the low interest of students’ learning in history subject, which was 38.73%. The purpose of this study is to determine the implementing of the Quantum Teaching model in order to increase students' learning interest in history subject. This type of research is classroom action research. The subject of this research was students of class X IPS 2. The technique of collecting data and instrument research is to use observation techniques using observation sheets of students’ learning interest. This study consisted of 2 cycles where there were 2 meetings in each cycle. The data analysis technique in this study uses percentage analysis techniques which then the results of the data are given meaning. The results of this study indicate that the Quantum Teaching model can increase students’ learning interest where in each cycle there is an increase in students’ learning activities from 38.73% in the initial observation to 66.97% in the first cycle and increase 85.96% in the second cycle. The increase occurred in each indicator of learning interest both on indicators of interest, involvement, feelings of pleasure and interest in learning history. Because of increasing the percentage in learning of each aspects of learning activities in each cycle, this research was stopped in the second cycle. It was stated that the Quantum Teaching model could increase students' interest in learning history subject.